2018
DOI: 10.1103/physrevlett.120.045001
|View full text |Cite
|
Sign up to set email alerts
|

Adiabatic Expansion of Electron Gas in a Magnetic Nozzle

Abstract: A specially constructed experiment shows the near perfect adiabatic expansion of an ideal electron gas resulting in a polytropic index greater than 1.4, approaching the adiabatic value of 5/3, when removing electric fields from the system, while the polytropic index close to unity is observed when the electrons are trapped by the electric fields. The measurements were made on collisionless electrons in an argon plasma expanding in a magnetic nozzle. The collision lengths of all electron collision processes are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 28 publications
(32 reference statements)
1
35
0
Order By: Relevance
“…This study has great significance in that it is capable of explaining the formation of non-locally behaving Druyvesteyn-like distribution, which has been consistently observed in the research groups worldwide, as well as the locally behaving Maxwellian distribution found in other groups with the consideration of the non-locally behaving confined electrons. Especially, this study is significant to present a new perspective that various values of polytropic index observed in the laboratory MN of each research group [15,33,34,37] could be the result of the difference in bounce region of the isothermally behaving confined electrons determined by the strength and configuration of the magnetic field. From another point of view, our results indicate that it is possible to control the eepf within the magnetically expanding plasma generated by the ECR or helicon sources by changing the bounce region of confined electrons according to the magnetic field conditions.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…This study has great significance in that it is capable of explaining the formation of non-locally behaving Druyvesteyn-like distribution, which has been consistently observed in the research groups worldwide, as well as the locally behaving Maxwellian distribution found in other groups with the consideration of the non-locally behaving confined electrons. Especially, this study is significant to present a new perspective that various values of polytropic index observed in the laboratory MN of each research group [15,33,34,37] could be the result of the difference in bounce region of the isothermally behaving confined electrons determined by the strength and configuration of the magnetic field. From another point of view, our results indicate that it is possible to control the eepf within the magnetically expanding plasma generated by the ECR or helicon sources by changing the bounce region of confined electrons according to the magnetic field conditions.…”
Section: Discussionmentioning
confidence: 90%
“…Similar to previous study [34], the study showed a self-generating ambipolar potential with isothermally behaving electrons. However, by removing boundary potential, which mainly confines the electrons in the device, perfect adiabatic expansion occurred without the formation of ambipolar potential in a diffusion region [37]. Even though the explanations of above groups are successful to interpret their own experimental results, the correlation between the change in γ e and the nozzle characteristics that will support their claims on the fundamental understanding on the different value of γ e is still not given in laboratory experiments.…”
Section: Introductionmentioning
confidence: 99%
“…4 and 5(b), the energy fluxes estimated from Eqs. (9) and (10) are plotted by open and filled squares, respectively, in Fig. 6 for (a) I B = 0 A, (b) 5 A, (c) 10 A, and (d) 15 A cases.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the normalized power P w /P abs based on Eqs. (9) and (10) are also plotted by open and filled squares, respectively. Since these equations correspond to the upper and lower limits of the power estimation, the actual loss power and normalized power would be in the colored region in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…in the present experiment. The whole structure of the plasma source can be biased by inserting the bipolar power supply (V bias ) between the discharge chamber and the plasma grid for the control of the plasma potential with respect to the PG, being similar to [20,21]. The positive ion beam can be extracted and accelerated from the plasma source by applying extraction and acceleration voltages V ext and V acc between the EG and PG and between the GG and EG, respectively, where V ext =1.5 kV and V acc =8 kV are chosen in the present experiment.…”
Section: Methodsmentioning
confidence: 99%